Processing sweet potatoes into french fries - Button, Kimberly (Kansas State University, 2015)
Sweet potatoes are a significant crop and are popular among consumers, particularly as french fries. Because the processing steps of making white potato french fries may be detrimental to the quality of a sweet potato fry, it is important to understand the impact of processing on quality and consumer acceptability. The variety of sweet potatoes can affect the texture, appearance, and consumer preference. Peeling processes have evolved from harsh lye treatments to more quick and efficient methods such as steam peeling. Blanching is one of the most important steps because it deactivates enzymes, including polyphenol oxidase and amylases, that affect texture and appearance. While hot water blanching is used by majority of french fry manufacturers, novel techniques like microwave blanching may be similarly effective and less detrimental to the texture and nutritional composition. Time and temperature of the blanching method can affect the texture and flavor by weakening cell walls and leaching sugars. Drying of sweet potato fries prepares the product prior to frying. Drying drives moisture off and allows the starch on the surface of the fries to gelatinize. Many types of dryers, including vacuum, hot air, and fluidized bed, have been evaluated for the rate of moisture loss and final product texture. Drying should not be done too quickly because case hardening will occur and make the product have a tough and chewy bite. Frying uses oil at elevated temperatures to develop color, flavor, and a crispy external texture. The type of oil, oil temperature, and time of frying will affect the finished product attributes. Low oil temperature may lead to higher oil uptake into the sweet potato fries. Vacuum frying compared to deep fat frying can create sweet potato fries with less darkening and less oil uptake, but this method would be difficult in large scale manufacturing. Opportunities in creating high quality sweet potato french fries are directly related to consumer acceptability and manufacturing capability.
Keywords: Sweet potato; Peeling; Blanching; Polyphenol oxidase; Drying; Frying; Food Science (0359)